Airflow Synergistic Needleless Electrospinning of Instant Noodle‐like Curly Nanofibrous Membranes for High‐Efficiency Air Filtration. Issue 14 (14th February 2022) - Yang, Zihao; Zhang, Xunlong; Qin, Zhikun; Li, Han; Wang, Jian; Zeng, Guangyong; Liu, Chunhai; Long, Jianping; Zhao, Yixia; Li, Yafang; Yan, Guilong
Abstract: Particulate matter (PM) pollution has become a serious environmental concern. Nanofibrous filters are widely reported to remove PM from polluted air. Herein, efficient and lightweight PM air filters are presented using airflow synergistic needleless electrospinning composed of auxiliary fields such as an airflow field and a secondary inductive electric field. Compared to needleless electrospinning with other spinnerets, it significantly improves productivity, fiber diameter, and porosity of fibrous air filters. The instant noodle‐like nanofiber structure can also be controlled by adjusting the airflow velocity. These air filters exhibit high (2.5 μm particulate matter) PM2.5 removal efficiency (99.9%) and high (0.3 μm particulate matter) PM0.3 removal efficiency (99.1%), low pressure drop (56 Pa for PM2.5 and 78 Pa for PM0.3 ), and large dust holding capacitance (the maximum value is 168 g m −2 for PM2.5, while 102 g m −2 for PM0.3 ). Meanwhile, the proposed PM filters are also tested suitable and stable to other polluted air filtrations such as cigarette smoke and sawdust. The large‐scale synthesis of such an attractive nanofiber structure presents the great potential of high‐performance filtration/separation materials. Abstract : The excellent filtration performance of PVA curly nanofibrous membrane for particulate matter removal is attributed to the synergistic regulation of auxiliary airflow field on the formation of nanofibers, which causes the fibers to form a three‐dimensional curly structure similar to instant noodles.